Demographic Profile and Risk Factors for Dry Eye - Basnet, Pragya; Basnet, Anjila; Karki, Poojyashree (Nepalese Medical Journal, 2018)
Correction: In the publication study period was missed. Study period "from 1st June 2017 to 30th November 2017" has been added. Introduction: Dry eye is a disorder of the tear film which occurs due to tear deficiency or excessive tear evaporation. It causes damage to the interpalpebral ocular surface and is associated with a variety of symptoms reflecting ocular discomfort. Materials and Methods: This was a hospital-based prospective observational study conducted to study the demography of dry eye patients and associated attributable risk factors for the disease. Every patient presenting with symptoms suggestive of dry eye was given a questionnaire, as per Salisbury Eye Evaluation Study and thorough ocular examination was done along with two tests for dry eye i.e Schirmer test I measuring less than 10mm and Tear film break up time measuring less than 10 sec. Final data analysis was done using statistical tool SPSS. Results: Demographic profile revealed a female preponderance in the patients with a ratio of 1.9:1. Amongst them, prevalence of premenopausal age was 53%. Dry eye was found to be more common in age group between 30 to 40 years (29%). The modifiable attributable risk factors were urban residence (67%), exposure to air condition and computer user (52%), indoor workers (59%), and environmental pollutants (60%). Conclusions: This study revealed the patients who presented with dry eye were mostly female of premenopausal age group, and exposed to modifiable risk factors which included residing at urban areas, indoor work, and exposure to environmental pollutants.